2019
DOI: 10.21608/ejnf.2019.79449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maca Administration on the Conception Rate and Reproductive Performance of Rabbit Does of Different Breeds.

Abstract: his work aimed to study the impact of Maca capsules administration on the conception rate and hormonal estimates of rabbit Does. Thirty six rabbit does, (12 V-line, 12 New Zealand white and 12 Bouscat), were divided equally into two equal groups 6 does per each. In the 1 st group, rabbits were fed a commercial breeder ration without any supplementation; while the 2 nd group was fed the commercial breeder ration and daily orally administered with 500mg Maca capsule/doe for one week before mating. All does in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Bilal et al [13] determined that the addition of 50 and 75 g/day of maca powder to racehorse rations had no effect on body weight and average daily feed consumption characteristics. In a study by El-Sheikh et al [14], the addition of maca to the diet did not have a significant effect on the live weight, daily feed consumption, litter size, litter weight or milk production of rabbits. To our knowledge, the only study examining the effects of adding maca to poultry diets was conducted by Korkmaz et al [15].…”
Section: Introductionmentioning
confidence: 87%
“…Bilal et al [13] determined that the addition of 50 and 75 g/day of maca powder to racehorse rations had no effect on body weight and average daily feed consumption characteristics. In a study by El-Sheikh et al [14], the addition of maca to the diet did not have a significant effect on the live weight, daily feed consumption, litter size, litter weight or milk production of rabbits. To our knowledge, the only study examining the effects of adding maca to poultry diets was conducted by Korkmaz et al [15].…”
Section: Introductionmentioning
confidence: 87%
“…Several studies have investigated its effects on ruminants ( 35 , 36 ), showing that the administration of Maca extract as a dietary supplement induced an increase in semen quality and the number of copulations and ejaculations. Other similar studies have been carried out in stallions ( 17 ), rabbits ( 41 ), poultry ( 42 , 43 ) and mice ( 16 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 81%
“…These positive effects may be due to maca's sterol bioactive components, such as campesterol (27.3%), ergosterol (13.6%), brassicasterol (9.1%), ∆7,22 -ergostadienol (4.5%), and sitosterol (45.5%), having phytoestrogen activity [54]. Recently, El-Sheikh et al [55] reported that oral treatment of maca capsules in rabbit does insignificantly affected the number of matings per conception, conception rate, and gestation length, and had no significant effects on the litter weight of maca-treated rabbit does at 7, 21, and 28 days; however, those at 14 days were insignificantly lower than the control group [49]. The disparities between this study and others may be due to the differences in the experimental animals' age, maca extract and its levels, exposure time, and experimental management.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Uchiyama et al [86] demonstrated that maca intake enhances serum LH levels in female rats. Recently, El-Sheikh et al [55] reported that maca-treated rabbit does have a numerically higher concentration of E2 hormone and a lower concentration of P4 hormone than those in the control group. This and the enhancement of serum LH levels may be the mechanisms that improve fertility [87].…”
Section: Discussionmentioning
confidence: 99%